The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1519/jsc.0000000000000800
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 8-Week High-Intensity Stretching Training on Biceps Femoris Architecture

Abstract: Previous studies have reported no changes on muscle architecture (MA) after static stretching interventions; however, authors have argued that stretching duration and intensity may not have been sufficient. A high-intensity stretching intervention targeting the knee flexors with an 8-week duration was conducted to observe the effects on biceps femoris long head (BF) architecture. Participants (n = 5) performed an average of 3.1 assisted-stretching sessions per week, whereas a control group (n = 5) did not perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
70
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(85 citation statements)
references
References 14 publications
(28 reference statements)
1
70
0
Order By: Relevance
“…With respect to the thigh musculature, Lima et al () found no significant benefit to performing 8 weeks of stretch training on both vastus lateralis FL (stretching: pre = 90 mm, post = 83 mm; control: pre = 78 mm, post = 69 mm) and biceps femoris FL (stretching: pre = 81, post = 78; control: pre = 88, post = 83 mm) in 24 healthy, physically active men (stretching group, n = 12; control group, n = 12). In a pilot study of 10 young adults (stretching group, n = 5; control group, n = 5), Freitas and Mil‐Homens () reported that 8 weeks of intense, long‐duration (450 s per set), passive stretch training had no effect on PA ( p = .13), but increased biceps femoris FL of 13.7% when compared with baseline's value ( p = .04), whereas no significant differences were seen in a non‐training control group. Although the ability to draw strong inferences from these data was limited by the low sample size (5 subjects each group), it should be noted that stretch training‐induced increases in FL were higher than the minimal detectable change.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to the thigh musculature, Lima et al () found no significant benefit to performing 8 weeks of stretch training on both vastus lateralis FL (stretching: pre = 90 mm, post = 83 mm; control: pre = 78 mm, post = 69 mm) and biceps femoris FL (stretching: pre = 81, post = 78; control: pre = 88, post = 83 mm) in 24 healthy, physically active men (stretching group, n = 12; control group, n = 12). In a pilot study of 10 young adults (stretching group, n = 5; control group, n = 5), Freitas and Mil‐Homens () reported that 8 weeks of intense, long‐duration (450 s per set), passive stretch training had no effect on PA ( p = .13), but increased biceps femoris FL of 13.7% when compared with baseline's value ( p = .04), whereas no significant differences were seen in a non‐training control group. Although the ability to draw strong inferences from these data was limited by the low sample size (5 subjects each group), it should be noted that stretch training‐induced increases in FL were higher than the minimal detectable change.…”
Section: Resultsmentioning
confidence: 99%
“…The purpose of this review was to evaluate the effect of stretch training on inducing muscle hypertrophy based on data from the literature. Of the 10 studies that met inclusion criteria, 3 observed positive effects in some measure of muscle growth (Freitas & Mil‐Homens, ; Mizuno, ; Simpson et al, ). Therefore, it is suggested that the stretch training can induce muscle hypertrophy; however, the way that the stretching is performed seems to influence the adaptations.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, longer GM fascicles in dancers compared to controls suggests a greater number of sarcomeres in series, which has implications for contractile function through an altered force‐length relationship . In line with these results, human intervention studies have measured increased GM fascicle length following stretching training . In vivo, true fascicle resting length and number of sarcomeres in series cannot be assessed.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the same studies did not find isometric and passive torque changes when 90s and 120s stretching volume was performed. On the other hand, when the stretching volume was augmented to 450s per session, it was detected an increase in the muscle fascicle length but they did not assess the torque (Freitas & Mil-homens, 2015). Thus, the increase in the fascicle length might depend on the stretching volume.…”
Section: Dicussionmentioning
confidence: 95%